Karakterisasi Biokomposit Polylactic Acid-Pati Jagung dengan Variasi Komposisi dan Bentuk Serat Jerami Padi untuk Disposable Tableware - Ilham Nur Hidayat (Fakultas Teknik, 2026)
The increasing use of single-use plastics has driven the development of environmentally friendly materials, including biocomposites based on Polylactic Acid (PLA). The incorporation of corn starch and rice straw as natural fillers offers the potential to improve biodegradability while utilizing abundant agricultural waste. This study aimed to investigate the effect of composition variation and rice straw reinforcement forms on the mechanical properties, biodegradability, and morphology of PLA-corn starch biocomposites for disposable tableware applications. The biocomposites were fabricated using the solvent casting method with the addition of 5% corn starch and rice straw reinforcements in the form of particles (PJP) and fibers (SJP) at volume fractions of 3%, 4%, 5%, and 6%. Characterization was conducted through tensile testing according to ASTM D638, biodegradation testing based on ASTM D5988, and morphological analysis using Scanning Electron Microscopy (SEM). The results showed that both composition variation and reinforcement form significantly influenced the mechanical properties and biodegradability of the biocomposites. The highest tensile strength and modulus of elasticity were achieved by the 5% PJP specimen, reaching 2.70 MPa and 341.32 MPa, respectively. Meanwhile, the highest elongation at break was observed in the 4% PJP specimen with a value of 2.03%. SEM analysis revealed that particle-reinforced biocomposites exhibited more homogeneous filler dispersion and better interfacial adhesion than fiber-reinforced biocomposites. Furthermore, the incorporation of corn starch and rice straw enhanced the biodegradability of PLA. Based on the overall performance, the PLA-corn starch biocomposite reinforced with 5% rice straw particles demonstrated the most favorable characteristics and shows potential as an environmentally friendly material for disposable tableware applications.
Finalisasi 1 Juli 2026_Yudi
Keywords: Biokomposit; Polylactic Acid (PLA); pati jagung; jerami padi; Disposable Tableware.